Quentin Skinner and the Cambridge School (Papeles, 2014)
The contemporary world which has lost some of its conceptual horizons due to strong movement of liquid postmodernity requires turning his gaze to the contributions of the past as a way to reinvent the humanist tradition and return to the axiological dimensions which would at least allow the construction of the 21st century alongside the ideas of good governance. In this sense, one of the fundamental contributions that can be viewed from hindsight, is related to the history of political thought and ideas of the Cambridge School of London. Knowing their origins and one of its greatest representatives: Quentin Skinner, will be vital, especially for Spanish-speaking society that has now made the commitment to become a point of reference for the world.
Keywords: Cambridge School; Quentin Skinner; ideas history; political thought; good governance